Gospodarske cone - Čok, Gregor (Urbani izziv, 2003)
The ongoing establishment of new economic zones reflects specific needs of local entrepreneurs that are searching for places to ensure or expand their operation. Differing definitions of the newly established areas for production, retail and services point out that the present entrepreneurial trend is directed into a wide palette of activities, but physical planners arehowever trying to define them in the same framework. Undefined terminology and relatively dispersed creation of new zones are mainly the consequence of vague planning strategies (national and regional), which when dealing with newor revitalised zones don't define real numbers, sizes and typologies.
Keywords: business zones; environmental effects; gospodarske cone; industrija; mala podjetja; prostorsko planiranje; prostorsko urejanje; razvojna strategija; spatial planning; spatial strategy